Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1007/s11060-021-03726-6
|View full text |Cite
|
Sign up to set email alerts
|

Useful hearing preservation is improved in vestibular schwannoma patients who undergo stereotactic radiosurgery before further hearing deterioration ensues

Abstract: IntroductionThe present study evaluates whether hearing deterioration during observation reduces serviceable hearing preservation rates after stereotactic radiosurgery (SRS) in vestibular schwannoma (VS) patients with useful hearing. MethodsWe retrospectively analyzed 1447 VS patients who underwent SRS between 1992 to 2017. We identi ed 100 VS patients who had Grade I Gardner-Robertson (GR) hearing at initial diagnosis but were observed without surgery or SRS. We compared hearing after SRS in 67 patients who r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…Sporadic and NF2-associated VSs seem to share this observation. 25 We attribute these results to the natural history of the vestibulocochlear nerve and its observed deterioration with old age. The hearing decline represents the main symptom of VS presentation among patients with NF2, with high rates of serviceable hearing loss.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Sporadic and NF2-associated VSs seem to share this observation. 25 We attribute these results to the natural history of the vestibulocochlear nerve and its observed deterioration with old age. The hearing decline represents the main symptom of VS presentation among patients with NF2, with high rates of serviceable hearing loss.…”
Section: Discussionmentioning
confidence: 80%
“…8,10,23,24 Our NF2 outcome data confirmed lower serviceable hearing preservation rates than the results obtained in patients with sporadic VSs. [25][26][27][28] However, the reason for hearing deterioration in VSs, especially among patients with NF2, is likely multifactorial and remains largely unclear.…”
Section: Tumor Control and Serviceable Hearing Preservationmentioning
confidence: 99%
“…17 Several studies have suggested that early intervention may improve serviceable hearing retention. 18,19 In a previous study reported from our institution, Akpinar et al 19 reported that early radiosurgery was associated with better hearing preservation rates. In this study, we had a median interval between VS diagnosis and SRS of 23 months (IQR, 1-51).…”
Section: Hearing Preservation and Time Of Treatmentmentioning
confidence: 89%
“…Because of the association between postradiation long-term serviceable hearing and better preintervention hearing, some centers advocate for early, upfront radiation (48)(49)(50) even in the absence of hearing loss or tumor growth. However, there are several considerations to address with this approach.…”
Section: Review Of Contemporary Literaturementioning
confidence: 99%